Review: Brian Kleiner, Isabell Renschler, Boris Wernli, Peter Farago & Dominique Joye (Eds.) (2013). Understanding Research Infrastructures in the Social Sciences - Katharina Manderscheid (Forum: Qualitative Social Research, 2014)
Research infrastructures constitute an essential part of social sciences research which, however, is under-represented in the public and scientific consciousness. Nevertheless, research infrastructures are significantly involved in producing, documenting and archiving data; in the development of standards; and in social sciences data skills training. The edition under review, which was developed from a symposium with the Swiss Centre of Expertise in the Social Sciences (FORS), aims at making research infrastructures and their services more visible, as well as highlight the necessity of their sustainable funding.